Respiratory Syncytial Virus Bronchiolitis in Infancy: The Acute Hospitalization Cost - Bozzola, Elena; Ciarlitto, Claudia; Guolo, Stefano; Brusco, Carla; Cerone, Gennaro; Antilici, Livia; Schettini, Livia; Piscitelli, Anna Lucia; Chiara Vittucci, Anna; Cutrera, Renato; Raponi, Massimiliano; Villani, Alberto (Frontiers in Pediatrics, 2021)
Introduction. Respiratory syncytial virus (RSV) bronchiolitis is among the leading causes of hospitalization in infants. Prophylaxis with palivizumab may reduce RSV infection but its prescription is restricted to high risk groups. Aim of the study is to retrospectively determine acute hospitalization costs of bronchiolitis. Materials and methods. Infants aged 1 month-1 year, admitted to Bambino Gesù Children Hospital, Rome, Italy, with a diagnosis of bronchiolitis from January 1st till December 31 th 2017 were included in the study. Results. 531 patients were enrolled in the study, with a mean age of 78.75 days. The main etiologic agent causing bronchiolitis was RSV, accounting for the 58.38% of infections. The total cost of bronchiolitis hospitalization was 2958786 euros. The mean cost per patient was significantly higher in case of RSV (5753.43 ± 2041.62 euros) compared to other etiology (5395.15 (± 2040.87euros) (p=0.04). Discussion. The study confirms the high hospitalization cost associated to bronchiolitis. In details, in case of RSV etiology, the cost was higher compared to other etiology, likely due to the longer hospitalization and the more frequently admission to intensive cure department. Conclusion. This study highlights that bronchiolitis is an important cost item even in a tertiary hospital.